Persepsi Generasi Muda dalam Keberlangsungan Tradisi sedekah Desa di Desa Candi, Kabupaten Sragen - Diajeng Putri Prasetyawati; Hannan Fuad Kholis; Maharani Miftahul Nuha (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Technological developments made a shift in the implementation of Sedekah desa. Youth as the next generation of cultural preservation is important to pay attention to cultural preservation such as the Sedekah desa tradition in Candi Village, Bentak, Sidoharjo, Sragen. This study aimed to determine the perception and involvement of the young generation of Candi Village related to the Sedekah Desa tradition. The research method used is a descriptive qualitative research method with a case study approach. Based on the results of the study, it shows that the younger generation does not know and understand the Sedekah desa tradition in Candi Village, Sragen Regency, and the awareness of youth involvement in the implementation of Sedekah Desa tradition activities is only based on the delegation of social responsibility from parents.